2020
DOI: 10.21608/jabps.2020.22937.1068
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes and PEGylated liposomes as drug delivery system

Abstract: Generally, it has been thought that PEG-conjugated nanocarriers are non-immunogenic. However, many reports have revealed that unexpected immune responses occur with such PEG-conjugated nanocarriers. The Most important one is the rapid clearance of PEGylated nanocarriers upon repeated administration which is called accelerated blood clearance phenomenon involving the production of antibodies against nanocarrier components, which reduces the safety and effectiveness of the encapsulated therapeutic agent. Such im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 67 publications
0
4
0
11
Order By: Relevance
“…The improvement in the healthy state of this group is indicative that the PEGylated CNTs could reduce inflammation in ischemic stroke leading to a healthy state of the rat. This also implies that PEG facilitated the delivery of the CNTs to the ischemic site [ 32 ]. From the results obtained, it could be deduced that CNTs have a beneficial role in the healing of stroke.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement in the healthy state of this group is indicative that the PEGylated CNTs could reduce inflammation in ischemic stroke leading to a healthy state of the rat. This also implies that PEG facilitated the delivery of the CNTs to the ischemic site [ 32 ]. From the results obtained, it could be deduced that CNTs have a beneficial role in the healing of stroke.…”
Section: Resultsmentioning
confidence: 99%
“…przyłączanie polimerów czy ligandów. Preparaty oparte na liposomach stają się wtedy bardziej neutralne dla organizmu, a ich zastosowanie bardziej wydajne [9][10][11][12].…”
Section: źRódło: Opracowanie Własneunclassified
“…Ograniczeniem w stosowaniu liposomów konwencjonalnych okazała się odpowiedź immunologiczna organizmu -po podaniu preparatu dochodziło do szybkiej eli- minacji podanej substancji z krwi. Doprowadziło to do ograniczenia stosowania tego typu liposomów na rzecz tych ze zmodyfikowaną otoczką, które nie są tak szybko wykrywane i usuwane przez składniki układu odpornościowego [7,9,10,21]. Dobrym zamiennikiem dla liposomów konwencjonalnych okazały się liposomy stabilizowane sterycznie, które w swojej otoczce zawierają dodatkowy związek, najczęściej jest to polimer -glikol polietylenowy PEG.…”
Section: Klasyfikacja Liposomów W Oparciu O Budowę Otoczkiunclassified
“…Cholesterol is added to increase the liposomal membrane fluidity, and polyethylene glycol (PEG) is added to increase the stability of liposomes in circulation and are commonly known as PEGylated liposomes. PEG protects liposomes from macrophages engulfment (by keeping the macrophages away from the liposomes) , - by probability 50% of the PEG molecules are inside the liposomes are 50% are outside. In addition, the type of phospholipid used determines the surface-charge of the liposome, and it has been shown that neutral liposomes (such as DOPC) help avoid rapid macrophage engulfment as well. , Although roto-evaporation is the conventional method used to prepare liposomes, for therapeutic applications, where the liposome formulation must be sterile, the freeze-drying method is preferred …”
Section: Experimental Sectionmentioning
confidence: 99%